"Gulabi" Portrayal in Vaidehi's "Gulabi Talkies and Short Waves": A Feministic Perspective - Mohammed Ahmed Saeed Al-Kaladi (English Education : English Journal for Teaching and Learning, 2022)
This study aims at analyzing the protagonist Gulabi in Vaidehi's short story  "Gulabi Talkies and  Short Waves" . " Gulabi Talkies and Short Waves" is one of the short stories in Vaidehi's short story collection Gulabi Talkies and Other Stories. The study tries to explore Vaidehi's style in portraying women characters showing her feminist attitude. So, the study analyses the main  character in the short story Gulabi pointing out the its characteristics as an implicit and explicit influencer  on the other women characters in the short story, on which this analysis sheds light on the work of Vaidehi as an Indian Feminist writer. The studies  begins by introducing the Indian  female novelist and short story writer Janaki Srinavasa Murthey. The study refers the historical background of  feminism emergence  as a movement and its emergence in literature globally and on the Indian level. The study refers to the main previous studies conducted on Vaidehi's short story collection. The study determine the methodology followed in conducting analysis of Gulabi character. The analysis of Gulabi is done in the discussion part where the character is analysed using the hints of the text of the short story. The study is concluded by a summary of the analysis result of the short story text.